STRATEGI OPERASI BIODIGESTER DENGAN SUBSTRAT INHIBITOR LIMONEN DAN TANIN DARI SAMPAH BUAH - Rahmanta, Anugrah Perdana (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
The amount of domestic waste generation is an urgent problem in many places in Indonesia. Managing fruit waste into biogas is one solution to the waste problem and also contributes to reducing the energy crisis. Some fruits contain inhibitors of methanogenic performance. Oranges contain limonene in addition to their acidity properties. Tannins in apples are also inhibitors of methanogens. Another group of microbes, namely acidogens and acetogens in the digester, are less sensitive to acid conditions and inhibitors. Special treatment is needed considering the sensitivity of methanogens to inhibitors originating from fruit waste. The strategy offered is to carry out the initial process of biodigester operation with the aim of maintaining the stability of growth and population of various microbial groups as reflected in the pH of the effluent, biogas volume and content of methane, TS and VS of both feed and biodigester effluent. The biodigester was designed semi-continuously on a pilot scale with an effective slurry volume of 16 liters with a loading rate of 40 kg/(m3.day). The feed was given at 6%TS. The composition of the substrate consists of a mixture of citrus fruits, apples and melons and mixed with cow dung in a certain ratio. The percentage of fruit substrate is increased gradually to give time for the microbial group in the biodigester to adapt to changes in inhibitor levels from fruit waste. Monitoring was conducted on pH, daily volume of biogas and methane levels, TS and VS of feed and effluent reflecting the performance of acidogen, acetogen and methanogen microbes. The average methane level was 62.15% and the highest was 75.63% in the S1 feed composition. The acclimatization time for each feed composition period varied between 14 to 65 days. Up to the composition of the fruit mixture of 35% (S5) or equivalent to a limonene content of 44.44 ppm, the pH stability parameter was depressed at a low value of 6.7.